2018
DOI: 10.1159/000489627
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Degeneration and Inhibition of Peripheral Nerve Regeneration in the SOD1-G93A Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Background: Myelination, degeneration and regeneration are implicated in crucial responses to injury in the peripheral nervous system. Considering the progression of amyotrophic lateral sclerosis (ALS), we used the superoxide dismutase 1 (SOD1)-G93A transgenic mouse model of ALS to investigate the effects of mutant SOD1 on the peripheral nerves. Methods: Changes in peripheral nerve morphology were analyzed in SOD1 mutant mice at various stages of the disease by toluidine blue staining and electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…SCs in ALS expressed significant levels of CSF1, IL‐34, and SCF and spatially interacted with immune effector cells bearing CSF‐1R and c‐Kit, suggesting a complex cellular interplay leading to local inflammation. Previous studies have shown infiltrating macrophages, mast cells and neutrophils (Chiu et al, ; Nardo et al, ; Trias et al, ) as well as SC proliferation (Deng et al, ) in the sciatic nerve of rodent ALS models. Here, we identified that these immune effectors express CSF‐1R and c‐Kit in human ALS nerves.…”
Section: Discussionmentioning
confidence: 94%
“…SCs in ALS expressed significant levels of CSF1, IL‐34, and SCF and spatially interacted with immune effector cells bearing CSF‐1R and c‐Kit, suggesting a complex cellular interplay leading to local inflammation. Previous studies have shown infiltrating macrophages, mast cells and neutrophils (Chiu et al, ; Nardo et al, ; Trias et al, ) as well as SC proliferation (Deng et al, ) in the sciatic nerve of rodent ALS models. Here, we identified that these immune effectors express CSF‐1R and c‐Kit in human ALS nerves.…”
Section: Discussionmentioning
confidence: 94%
“…On the second day, the sections were incubated with the secondary antibody and the third antibody, then incubated for 2 minutes with diaminobenzidine solution and observed under a microscope. In addition, the gastrocnemius muscle and tibialis anterior muscle were cut into 10 μm sections and stained with hematoxylin and eosin, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the gastrocnemius muscle and tibialis anterior muscle were cut into 10 μm sections and stained with hematoxylin and eosin, as previously described. 17…”
Section: Immunofluorescence and Immunohistochemical Stainingmentioning
confidence: 99%
“…Proliferation and the inflammatory micro-environment were inhibited, which impaired the regeneration and remyelination of axons after crush injury in the SOD1-G93A mice. The mutant human SOD1 protein induced axonal and myelin degeneration during the progression of ALS and participated in axon remyelination -regeneration in response to injury [32].…”
Section: And In Neuroscience Field: Article Mindset Kinetics and Somementioning
confidence: 99%